Globalization and the environment risk assessment and the WTO - Robertson, David, 1935-; Kellow, Aynsley J. (Aynsley John), 1951-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2001)
One of the unforeseen consequences of the WTO agreements has been controversy over risk. This volume explores aspects of risk with special reference to the WTO, where national instruments to reduce risk may conflict with international trade rules. The book is divided into sections dealing with: accounting for risk in trade agreements; risk and the WTO; managing risk in policy making; negotiating experience with risk; national risks and quarantine standards; and managing biotechnology.
pt. 1. Risk and the WTO -- pt. 2. Managing risk in policymaking -- pt. 3. Negotiating experience with risk -- pt. 4. National risks and quarantine standards -- pt. 5. Managing biotechnology -- pt. 6. Concluding summary.
Papers presented at a two-day meeting at the Melbourne Business School in Feb. 1999.
Includes bibliographical references and index.
Keywords: World Trade Organization; Free trade -- Environmental aspects -- Congresses; International trade -- Environmental aspects -- Congresses; Environmental policy -- Congresses; Foreign trade regulation -- Environmental aspects -- Congresses; Risk management -- Congresses; Globalization -- Environmental aspects -- Congresses; Electronic books